Natural Frequencies of Isotropic Rectangular Plates in Improved Accuracy - Yoshihiro Narita (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
The objective of this paper is to present comprehensive lists of accurate natural frequencies of isotropic thin rectangular plates. For this purpose, a simple yet very accurate analytical approach is described to study the free vibration of the plates. In numerical computations, convergence and comparison studies are conducted to check accuracy of the present solution and to demonstrate improvement of numerical solutions in the results. Twenty-one tables are then provided to give the lowest six frequency parameters for all possible combinations of three typical edge conditions (clamped, simply supported and free edges). Each frequency value in the tables is given in five significant figures for non-Levy type problem (i.e., two opposite edges not simply supported) and six significant figures for Levy type problem. These results are presented for five different aspect ratios in the same format of the past representative reference.